Integration of Project-Based STEM Learning in the Meliuk Menerjang Material within the Emancipated Curriculum - Mardhatillah; Shirly Rizki Kusumaningrum; Ade Eka Anggraini; Siti Faizah; Muhammad Aidi Noor Ihsan; Lili Kasmini (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to develop a project-based STEM (Science, Technology, Engineering, and Mathematics) learning tool for the "Meliuk Menerjang" material in the Emancipated Curriculum for grade IV students in Indonesian elementary schools. The objective is to create a tool that is feasible, practical, and effective in improving student learning outcomes. The research employs a Research and Development (R&D) approach, specifically following the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Data was collected through validation from material and design experts, questionnaires, and student performance assessments. The study included 25 students and 20 teachers from various elementary schools in Malang City to identify the needs and effectiveness of the project-based STEM learning model. Data analysis was performed using SPSS for effectiveness analysis and qualitative analysis for feedback and validation results. Findings: The project-based STEM learning model demonstrated high feasibility with significant improvements in students' understanding and skills. Validation results showed that the content was relevant and supportive of STEM skill development. Both teachers and students positively accepted the learning model, indicating increased confidence and motivation. Conclusion: Integrating project-based STEM learning in the Emancipated Curriculum positively impacts student engagement, motivation, and learning outcomes. This approach fosters critical thinking, creativity, and teamwork among elementary students, preparing them for future technological challenges.